2022
DOI: 10.1101/2022.03.17.484653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fragment-Based Ligand Generation Guided By Geometric Deep Learning On Protein-Ligand Structure

Abstract: Computationally-aided design of novel molecules has the potential to accelerate drug discovery. Several recent generative models aimed to create new molecules for specific protein targets. However, a rate limiting step in drug development is molecule optimization, which can take several years due to the challenge of optimizing multiple molecular properties at once. We developed a method to solve a specific molecular optimization problem in silico: expanding a small, fragment-like starting molecule bound to a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The BindingNet data set can also be used to develop and benchmark ML-based models for binding affinity and binding pose prediction , and molecular generation. PDBbind is the most widely used training data set for ML methods, , and the binding affinity prediction performances of ML-based scoring functions on PDBbind have been reported with the R p around 0.8. However, the insufficient size and sparsity of PDBbind have resulted in poor generalization capability on out-of-distribution data sets. ,, Both Yang et al and Mastropietro et al have found that the ligand memorization often dominates the predictions of ML-based models. , In addition, Zhu et al performed an interpretable analysis of PDBbind-trained models in 2022 and revealed that these models rely on the buried SASA-related features to make predictions . Since the BindingNet data set has significantly increased the number of available complex structures, it would be interesting to explore the performance of ML models trained on BindingNet.…”
Section: Resultsmentioning
confidence: 99%
“…The BindingNet data set can also be used to develop and benchmark ML-based models for binding affinity and binding pose prediction , and molecular generation. PDBbind is the most widely used training data set for ML methods, , and the binding affinity prediction performances of ML-based scoring functions on PDBbind have been reported with the R p around 0.8. However, the insufficient size and sparsity of PDBbind have resulted in poor generalization capability on out-of-distribution data sets. ,, Both Yang et al and Mastropietro et al have found that the ligand memorization often dominates the predictions of ML-based models. , In addition, Zhu et al performed an interpretable analysis of PDBbind-trained models in 2022 and revealed that these models rely on the buried SASA-related features to make predictions . Since the BindingNet data set has significantly increased the number of available complex structures, it would be interesting to explore the performance of ML models trained on BindingNet.…”
Section: Resultsmentioning
confidence: 99%
“…Later works used diffusion models, [126,127] variational autoencoders, [118] and reinforcement learning [119,120,128] to directly generate ligand conformations inside the binding pocket. Recently, equivariant neural networks coupled with point-cloud representations have been used for molecule optimization, via pocket-based fragment expansion, [200] as well as generative adversarial networks that represent proteins at the atomic level. [129] Compared to 3D graphs, molecular strings are usually easier to generate and might match or outperform graph-based models.…”
Section: Protein-based De Novo Molecule Designmentioning
confidence: 99%
“…By contrast, Fialková et al (2021), Li et al (2021), Thomas et al (2021), Fu et al (2022)use approaches based on reinforcement learning. Other works include fragment-based ligand generation, in which new molecular fragments are sequentially attached to the growing molecule (Powers et al 2022); abstraction of the geometric interaction features of the receptor-ligand complex to a latent space, for generative models such as Bayesian sampling (Wang et al 2022b) and RNNs (Zhang and Chen 2022); and use of experimental electron densities as training data for the conditional generative model (Wang et al 2022a).…”
Section: Related Workmentioning
confidence: 99%